The Influence of Local Dialects on Phonological Errors in the Arabic Language: Ta’thīr al-Lahajāt al-Maḥalliyyah ʿalā al-Akhtāʾ al-Fūnūlūjiyyah fī al-Lughah al-ʿArabiyyah - Salbiah, Rahma; Intan Wahyuni; Rosalinda (An-Nahdah Al-'Arabiyah, 2026)
Arabic language education is an important field of education in improving Arabic language and culture skills. However, many challenges remain in the Arabic language learning process, one of which is the error of makharijul huruf. To learn Arabic, we should be able to understand the letters contained in Arabic itself; the hijaiyah letters are the main letters for spelling and reading Arabic texts. This research is motivated by the phenomenon of students from the Singkil area who experience difficulties in reading Arabic texts with correct makhraj. The purpose of this study is to describe the influence of the village lahjah on errors in makharijul huruf forms in Arabic learning, especially when reading Arabic texts. The research method used is descriptive qualitative so that researchers can explain in depth the errors made by students. The data in this study comes from audiovisual recordings of students majoring in Arabic Language Education (PBA) at Al Washliyah University Darussalam Banda Aceh (UNADA) while reading Arabic texts. The factors causing these errors include environmental habits, the influence of their first language in the form of the Singkil dialect, learning motivation, and difficulty in correctly identifying the makhraj position. The novelty of this research lies in the mapping of specific phonetic distortion patterns due to phonemic interference in the Singkil dialect which has not been widely explored in previous studies, thus theoretically providing a significant contribution to the development of phonological theory.   ُعدّ تعليم اللغة العربية مجالًا هامًا في التعليم، إذ يُسهم في تحسين مهارات اللغة والثقافة العربية. ومع ذلك، لا تزال هناك تحديات عديدة في عملية تعلّم اللغة العربية، من بينها أخطاء مخارج الحروف. ولتعلّم اللغة العربية، ينبغي فهم الحروف الموجودة فيها؛ فالحروف الهجائية هي الحروف الأساسية في تهجئة وقراءة النصوص العربية. وقد استُلهم هذا البحث من ظاهرة طلاب منطقة سينكيل الذين يواجهون صعوبة في قراءة النصوص العربية بمخارج حروف صحيحة. وتهدف هذه الدراسة إلى وصف تأثير اللهجة المحلية على أخطاء مخارج الحروف في تعلّم اللغة العربية، لا سيما عند قراءة النصوص العربية. وقد استُخدم في البحث المنهج الوصفي النوعي، ما يُتيح للباحثين شرح الأخطاء التي يرتكبها الطلاب شرحًا وافيًا. وتستند بيانات هذه الدراسة إلى تسجيلات سمعية بصرية لطلاب تخصص تعليم اللغة العربية في جامعة الوشلية دار السلام باندا آتشيه (UNADA) أثناء قراءتهم للنصوص العربية. تشمل العوامل المسببة لهذه الأخطاء العادات البيئية، وتأثير لغتهم الأم المتمثلة في لهجة سينكيل، ودافعية التعلم، وصعوبة تحديد موضع حرف الماخراج بدقة. تكمن جدة هذا البحث في تحديد أنماط التشوه الصوتي المحددة الناتجة عن التداخل الصوتي في لهجة سينكيل، وهو موضوع لم يُدرس على نطاق واسع في الدراسات السابقة، مما يُسهم نظريًا إسهامًا كبيرًا في تطوير النظرية الصوتية.   Pendidikan bahasa Arab merupakan salah satu bidang pendidikan yang penting dalam meningkatkan kemampuan bahasa dan budaya Arab. Namun, masih banyak tantangan yang dihadapi dalam proses pembelajaran bahasa Arab, salah satunya adalah kesalahan makharijul huruf. Untuk mempelajari bahasa Arab, kita semestinya dapat mengetahui huruf-huruf yang terdapat pada bahasa Arab itu sendiri; huruf hijaiyah merupakan huruf utama untuk mengeja dan membaca teks berbahasa Arab. Penelitian ini dilatarbelakangi oleh fenomena mahasiswa yang berasal dari daerah Singkil yang mengalami kesulitan dalam membaca teks Arab dengan makhraj yang benar. Tujuan penelitian ini adalah untuk mendeskripsikan pengaruh lahjah kampung terhadap kesalahan bentuk-bentuk makharijul huruf dalam pembelajaran bahasa Arab, khususnya ketika membaca teks bahasa Arab. Metode penelitian yang digunakan adalah kualitatif deskriptif agar peneliti dapat menjelaskan secara mendalam kesalahan-kesalahan yang dilakukan oleh mahasiswa. Data pada penelitian ini bersumber dari hasil rekaman audiovisual mahasiswa jurusan Pendidikan Bahasa Arab (PBA) Universitas Al Washliyah Darussalam Banda Aceh (UNADA) saat membaca teks bahasa Arab. Adapun faktor penyebab kesalahan tersebut meliputi kebiasaan lingkungan, pengaruh bahasa pertama berupa dialek Singkil, motivasi belajar, serta kesulitan mengidentifikasi letak makhraj dengan benar. Kebaruan penelitian ini terletak pada pemetaan pola distorsi fonetis yang spesifik akibat interferensi fonemik dialek Singkil yang belum banyak dieksplorasi dalam studi terdahulu, sehingga secara teoretis memberikan kontribusi signifikan terhadap pengembangan teori fonologi.